ENVIRONMENTAL QUALITY IN INDONESIA BASED ON ISLAMIC BANK FINANCING AND ECONOMIC GROWTH - Nengsih, Titin Agustin; Kurniawan, Bambang; Saputra, Indra (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
Banking activities both conventional and sharia banks in Indonesia are currently growing rapidly. This condition is marked by an increase in the value of an area's assets and an increase in the value of financing every year. These increases support economic activity quickly but can also cause environmental degradation impacts such as increasing the value of CO2 emissions (pollution). This study aims to determine how much influence Islamic financing and economic growth have on environmental quality in Indonesia. A quantitative approach with Multiple linear Regression was applied in this study. The results showed that Islamic bank financing and economic growth have a significant and negative effect on environmental quality in Indonesia.